Procedure Oriented Torsional Anatomy of the Forearm for Spasticity Injection. Issue 5 (September 2015) - Chiou-Tan, Faye; Cianca, John; John, Joslyn; Furr-Stimming, Erin; Pandit, Sindhu; Taber, Katherine H.
<x xml:space="preserve">Abstract</x> This is the second in a series of articles related to the concept of "torsional" anatomy. The objective of this article is to provide musculoskeletal ultrasound (MSKUS) anatomy of the forearm in the position of hemispastic flexion as a reference relevant to needle procedures. Methods The MSKUS images were obtained in a healthy human subject. Marker dots were placed over common injection sites in the forearm for spasticity. The MSKUS probe was centered over each dot to obtain a cross-sectional view. A pair of MSKUS images was recorded for each site: the first in anatomic neutral and second in hemiparetic spastic position. The images were compared side to side. In addition, a video recording was made at each site to track the movement of the muscles and nerves during internal rotation. Results The pronator teres (PT) rotated medially and the brachialis and biceps tendon rotated in view. In addition, the median nerve became more superficial. The flexor carpi radialis rotated medially and was replaced by PT and the median nerve. The flexor carpi ulnaris and flexor digitorum profundus rotated medially and were replaced by the flexor carpi radialis, PT and median nerve. The flexor digitorum superficialis was replaced by the brachioradialis, extensor carpi radialis brevis, and radial nerve. The brachioradialis was replaced by the extensor carpi radialis brevis and extensor digitorum communis. Discussion Intended muscle targets rotate out of view and injection range. These are replaced by other muscles and nerves that could inadvertently be injected. This potentially could result in both increased complications and decreased efficacy of the procedure. Conclusions It is hoped that this series of images will increase the accuracy and safety of needle placement for spasticity injections in the forearm.